Influence of the first wave of COVID-19 on asthma inhaler prescriptions - C. I. Bloom (Nature Portfolio, 2021)
Abstract In the beginning of the COVID-19 pandemic, there were major concerns regarding the huge demand for asthma inhalers. Using the primary-care medical records for 614,700 asthma patients between January and June 2020, we found that there was a substantial increase in inhalers solely in March 2020. Patients significantly associated with receiving higher inhaled corticosteroid prescriptions were younger, of higher socioeconomic status, and had milder asthma.